The role of mitochondria in metastasis development: The role of mitochondria in metastasis development - Blagov, Alexander V.; Postnov, Anton Y.; Khotina , Victoriya A.; Sukhorukov , Vasily N.; Sadykhov , Nikolay K.; Orekhov , Alexander N. (Cellular and Molecular Biology, 2024)
Metastasis is a hallmark of cancer and is responsible for the largest number of cancer-related deaths. However, it remains poorly understood. Recently, evidence has accumulated pointing to the role of mitochondria in the metastatic spread of cancer cells. Mitochondria are dynamic organelles that have significant metabolic activity and are considered signaling centers with biosynthetic, bioenergetic, and signaling functions that control key biological pathways. Also, data were presented that mitochondria can influence all processes associated with oncogenesis, from malignant transformation to metastatic dissemination. The role of mitochondria in cancer progression/metastasis includes alteration of glycolysis, regulation of ROS, and suppression of intrinsic apoptosis. This review will summarize the current knowledge on the contribution of mitochondria to tumor cell invasion and dissemination and the possible mechanisms behind this. Mitochondrial-targeted therapeutic strategies to combat metastatic cancer will also be proposed.